Changes in soil chemical properties after long-term fertilization and crop residue incorporation in a maize-groundnut rotation system - Gill, Sylvia Sylvester.
A field study was established at Puchong farm, Universiti Putra Malaysia, which has been planted since 1996 to 2001 with sweet corn and groundnut using rotation system. The objective of this study was to determine the effects of inorganic and organic fertilizer with or without crop residue incorporation to the soil chemical properties after the establishemnt of ten crop cycles and fallowed for about five years. Three treatments were done on the plots under rotation system; (i) crop residue with recommended inorgainc fertilizer (T1), (ii) complete removal of crop residue with recommended inorganic fertilizer (T2), (iii) combination of inorganic fertilizer, chiken manure (10 t ha-1) and crop residue (T3). This study used the randomized complete block design (RCBD) with four replications for each treatment. Two depths of soil (0-15 cm and 15-30 cm) were used in this study. The chemical properties determined were soil pH, organic carbon, total nitrogen, available phosphorous, exchangeable K, Ca and Mg and Cation Exchange Capacity (CEC), Overall, no significant differences were found among the treatment means in all parameters determined. The fallow period probably contribute to such result because no organic matter or fertilizer was added. Overall, all treatments are able to produce a relatively similar effects on the soil chemical characteristics.